Vibrations of mechanical systems with regular structure - Banakh, Ludmilla; Kempner, Mark.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Vibrations in systems with a periodic structure is the subject of many ongoing research activities. This work presents the analysis of such systems with the help of the theory of representation groups by finite element methods, dynamic Compliance and dynamic rigidness methods, specially adjusted for the analysis of engineering structures. The approach presented in this book permits a simplification and facilitates the understanding of mechanical vibrations in various structures. The book includes extended studies of even complicated machinery structures with an emphasis on flight vehicle engines.
Mechanical Vibratory Systems with Hierarchical Structure. Simulation and Calculation Methods -- Systems with Lumped Parameters -- Vibrations of Regular Systems with Periodic Structure -- Vibrations of Systems with Geometric Symmetry. Quasi-symmetrical Systems -- Systems with Distributed Parameters -- Basic Equations and Numerical Methods -- Systems with Periodic Structure -- Systems with Cyclic Symmetry -- Systems with Reflection Symmetry Elements -- Self-Similar Structures -- Vibrations of Rotor Systems with Periodic Structure -- Vibrations of Regular Ribbed Cylindrical Shells.
Keywords: Engineering; Group theory; Numerical analysis; Mechanical engineering; Vibration; Engineering; Vibration, Dynamical Systems, Control; Group Theory and Generalizations; Numerical Analysis; Structural Mechanics; Automotive Engineering